2014
DOI: 10.3389/fphys.2014.00109
|View full text |Cite
|
Sign up to set email alerts
|

The status of and future research into Myalgic Encephalomyelitis and Chronic Fatigue Syndrome: the need of accurate diagnosis, objective assessment, and acknowledging biological and clinical subgroups

Abstract: Although Myalgic Encephalomyelitis (ME) and Chronic Fatigue Syndrome (CFS) are used interchangeably, the diagnostic criteria define two distinct clinical entities. Cognitive impairment, (muscle) weakness, circulatory disturbances, marked variability of symptoms, and, above all, post-exertional malaise: a long-lasting increase of symptoms after a minor exertion, are distinctive symptoms of ME. This latter phenomenon separates ME, a neuro-immune illness, from chronic fatigue (syndrome), other disorders and decon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 79 publications
(124 reference statements)
0
26
0
Order By: Relevance
“…The heterogeneity of the CFS patient group [23] due to its vague definition, is one of the important reasons why research into CFS [5] has not been very effective, yielding positive findings, no significant differences and contradictive results in CFS [9,24]. So, research into patients with “ME/CFS” [9], an even more heterogonous patient population than CFS [5], most likely will not yield any significant findings and discriminative abnormalities, which will “confirm” the incorrect perception [9] that ME [2,3,4], CFS [5], “ME/CFS” (SEID) [9] are “functional somatic syndromes” [25].…”
Section: Due To the New Definition Of “Me/cfs” The Four Recommendamentioning
confidence: 99%
“…The heterogeneity of the CFS patient group [23] due to its vague definition, is one of the important reasons why research into CFS [5] has not been very effective, yielding positive findings, no significant differences and contradictive results in CFS [9,24]. So, research into patients with “ME/CFS” [9], an even more heterogonous patient population than CFS [5], most likely will not yield any significant findings and discriminative abnormalities, which will “confirm” the incorrect perception [9] that ME [2,3,4], CFS [5], “ME/CFS” (SEID) [9] are “functional somatic syndromes” [25].…”
Section: Due To the New Definition Of “Me/cfs” The Four Recommendamentioning
confidence: 99%
“…To establish the presence and severity of symptoms and to assess the health status of patients impartially objective test measures are indispensable [51]. Subjective measures solely based on questionnaires, e.g.…”
Section: Using Objective Test Methods To Assess the Symptoms Improvementioning
confidence: 99%
“…repeated exercise tests [41,42], cognitive tests [43,44], tilt table tests [45,46], muscle power (endurance) tests [47,48], for diagnosing patients [49] and determining the effect of interventions [50], to find correlations between symptoms/subjective measures and objective test outcomes, and to define symptomatic subgroups of the ME and CFS patient population [51].…”
Section: A New Direction: Back To the Futurementioning
confidence: 99%
“…Although ME and CFS are often declared to be synonyms [4], the diagnostic criteria define two distinct clinical entities. ME is primarily defined by muscle weakness (and myalgia) after a minor exertion lasting for days and characteristic neurological features, while CFS is primarily defined by (unexplained, incapacitating) chronic fatigue [4].…”
mentioning
confidence: 99%
“…ME is primarily defined by muscle weakness (and myalgia) after a minor exertion lasting for days and characteristic neurological features, while CFS is primarily defined by (unexplained, incapacitating) chronic fatigue [4]. Although ME and CFS are to be considered to be two distinct, partially overlapping, diagnostic labels [4], the Institute of Medicine [5] confirmed that post-exertional "malaise", defined as a prolonged aggravation of typical symptoms (e.g. "brain fog"/ cognitive deficits and muscle and joint pain) is the hallmark feature of "ME/CFS".…”
mentioning
confidence: 99%